2008
DOI: 10.1016/j.yqres.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Age constraints on the late Quaternary evolution of Qinghai Lake, Tibetan Plateau

Abstract: Dating and geomorphology of shoreline features in the Qinghai Lake basin of northwestern China suggest that, contrary to previous interpretations, the lake likely did not reach levels 66–140 m above modern within the past ∼ 90,000 yr. Maximum highstands of ∼ 20–66 m above modern probably date to Marine Isotope Stage (MIS) 5. MIS 3 highstands are undated and uncertain but may have been at or below post-glacial highs. The lake probably reached ∼ 3202–3206 m (+ 8–12 m) during the early Holocene but stayed below ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 38 publications
5
85
2
3
Order By: Relevance
“…Most of these lakes are freshwater lakes [6], such as Lake Kushuihai, Tianshuihai, and Aksai Chin, which are located south of the western Kunlun Mountains. However, these characterizations have recently been challenged by data obtained from optically stimulated luminescence (OSL) and uranium series dating data, which are in obvious contrast with the above radiocarbon data [7,8]. For example, sediment from the same lacustrine facies in the Tengger Desert (to the northeast of the Tibetan Plateau) date back to 25-40 ka BP [9,10] according to radiocarbon dating, but OSL dating indicated that they were from 70-130 ka (MIS 5) [8].…”
Section: Alpine Lakes In the Frigid Tibetan Plateaumentioning
confidence: 99%
“…Most of these lakes are freshwater lakes [6], such as Lake Kushuihai, Tianshuihai, and Aksai Chin, which are located south of the western Kunlun Mountains. However, these characterizations have recently been challenged by data obtained from optically stimulated luminescence (OSL) and uranium series dating data, which are in obvious contrast with the above radiocarbon data [7,8]. For example, sediment from the same lacustrine facies in the Tengger Desert (to the northeast of the Tibetan Plateau) date back to 25-40 ka BP [9,10] according to radiocarbon dating, but OSL dating indicated that they were from 70-130 ka (MIS 5) [8].…”
Section: Alpine Lakes In the Frigid Tibetan Plateaumentioning
confidence: 99%
“…In the North and South Lake, Madsen et al [10] considered that lagoonal deposits at 3240 m ASL occurred between 94 and 102 ka, and lacustrine deposits (on the southwest shore) at 3205-3210 m ASL occurred at 95 ka. This was in the context of an absence of lacustrine deposits dating between 95 and 25 ka in the same locale, and an OSL deposit date of 38.8 ka on a sample that was from alluvial (not lacustrine) deposits [10]. They argued that maximum high-stands of 20-66 m above modern probably date to MIS 5, and MIS 3 high stands may have been at or below postglacial highs [10].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported high lake levels in different regions of China during the Late Quaternary; for example, the Hexi Corridor and Alxa Plateau [1][2][3][4][5][6][7], Xinjiang [8,9], and the Qinghai-Tibet Plateau [10][11][12][13][14][15][16][17][18][19]. These studies prove that lake levels were at their highest in northwest China during the late Pleistocene.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Meanwhile, a high lake level of Toson Lake during MIS3 was recorded at 31 ka (Fan et al, 2012). Furthermore, a large number of high paleo-shorelines have been identified along the southern margin of Qinghai Lake, and OSL dating results suggest that high lake levels that are~20 to 66 m above that of the modern lake occurred at~110-75 ka (Madsen et al, 2008;Liu et al, 2010;Rhode et al, 2010). Pollen record from Zoige Basin of eastern Tibetan Plateau indicate that coniferous forest expanded in the catchment of the Zoige Basin during last interglacial and some periods of last glacial (Chen et al, 1999).…”
Section: Regional Correlation and Possible Mechanismmentioning
confidence: 99%